The Effects of Xialiqi Capsules in Regulating the Pyroptosis of Prostate Epithelial Cells Via NLRP3/Caspase-1 Pathway for the Treatment of Chronic Prostatitis - Zhiming Hong; Zilong Chen; Wenshuo Chen; Junfeng Qiu; Shengjie Wang; Yi Wei; Jun Guo (American Journal of Men's Health)
Chronic prostatitis (CNP) is a prevalent inflammatory disorder among men. The Xialiqi capsule has been reported to alleviate the clinical symptoms of CNP patients, which may be related to its anti-inflammatory effect; yet, its exact mechanism of action remains unclear. In this study, human normal prostate epithelial cells (RWPE-2 cells) were categorized into a control group, a model group, an inhibitor group, along with high, medium, and low drug-containing serum groups (5%, 10%, and 15%, respectively). With the exception of the control group, cell pyroptosis models were created by stimulating with lipopolysaccharide (100 ng/mL) and adenosine triphosphate (5 mM). Subsequently, drug-containing serum and the NOD-like receptor 3 ( NLRP3 ) inhibitor (MCC950) were utilized to intervene with the model cells according to their respective groups. Post-administration of MCC950 and drug-containing serum, an improvement in cell viability was noted in the inhibitor group and medium-high dosage groups (by 20.5%, 38.2%, and 73.2%). Transmission electron microscopy indicated a reduction in the features characteristic of cell pyroptosis. Levels of nitric oxide, interleukin-18 (IL-18), and tumor necrosis factor-α in the cellular supernatant decreased significantly (60.7%, 21.6%, 33.7%, 41.8%; 49.2%, 54.8%, 53.5%, 69.3%; 31.3%, 44.4%, 38.1%, 51.2%). Immunofluorescence showed reduced fluorescence intensity of NLRP3 and Cysteine aspartate protease-1 (Caspase-1) proteins, and Western Blot analysis revealed a significant decline in the expression of NLRP3, pro-Caspase-1, and gasdermin D (20.5%, 45.9%, 58.1%, 74.8%; 23.2%, 36.7%, 51.6%, 51.9%; 15.4%, 28.6%, 33.1%, 39.2%). In vitro experiments suggest that the Xialiqi capsule may treat CNP by regulating prostate epithelial cell pyroptosis and reducing inflammatory factor release via inhibiting the NLRP3/Caspase-1 signaling pathway. This study offers a novel approach for future CNP treatment with traditional Chinese medicine preparations, deserving further promotion.